Sistem Monitoring Ruang Kosong pada Area Parkir Menggunakan Teknologi Internet of Things - Rian Ardiansyah; Mahishya Darizqhi Dyah Saputri; Haris Gibran Rizantha; nugrah Al Hafidz; Rafli Nur Ikhsan; Rahmat Fadillah; Indra Dwisaputra (Department of Electrical Engineering, UNJANI, 2025)
The increasing number of vehicles in urban areas has led to serious parking space issues, particularly in shopping centers, office complexes, and university campuses. The difficulty in locating vacant parking spots contributes to traffic congestion, fuel waste, and higher exhaust emissions. This study develops a parking lot monitoring system based on the Internet of Things (IoT), which detects vehicle presence in each parking slot in real time using sensors. The availability of parking spaces is displayed digitally, allowing drivers to find vacant spots without circling around. This system also enhances parking management efficiency by enabling centralized and automated monitoring of parking conditions. Implementation results show that the system effectively improves space utilization and significantly reduces the time required to find a parking spot.